Sub-chronic administration of St. John’s wort reverses anxiety- and depressive-like behaviors induced by two different protocols of chronic stress - Rojas Carvajal, Mijail (2017)
Introduction. St. John’s wort (Hypericum perforatum, HP) is one of the most used herbal medicines. Here we investigated the putative antidepressive- and anxiolytic-like effects of HP, by using a well-validated rat model of anxiety and depression based on chronic stress. Methods. To this purpose, subjects were either immobilized (INM) or randomly exposed to different stressors (chronic unpredictable stress: CUS) during 30 days. Forty-eight hours after the last stress session, subjects of each stress condition were randomly assigned to the HP (100 mg/kg), diazepam (5 mg/kg) or saline groups. Immediately after a baseline measure and during 10 consecutive days, drugs were intragastrically administrated. During this period, four open-field and elevated plus-maze tests were carried out every other day. Results. CUS and INM stress were found to induce an anxiety- and depressive-like phenotype in both tests, whereas HP and diazepam progressively restored this stress-dependent phenotype. HP potency was almost equivalent to that of the diazepam. However, diazepam peaked slightly sooner and remained unaltered throughout the testing days, whereas HP peaked gradually and required more administrations to reach diazepam levels. Conclusion. HP seems to be a promising alternative treatment for anxiety and mood disorders that may have wider safe-dosing ranges and fewer side-effects than benzodiazepines